The reading difficulties in Chinese for individuals with attention deficit hyperactivity disorder: the role of executive function deficits - Jia Wei; Dengxian Yang; Fang Cheng; Wenwu Zhang (PeerJ, 2025)
Background Attention-deficit/hyperactivity disorder (ADHD) and reading disability (RD) are prevalent childhood conditions that together affect millions of children worldwide. In China, the prevalence of ADHD is approximately 6.4%, whereas the prevalence of RD ranges from 3.45% to 8%. Approximately 18–45% of children with ADHD also display comorbid RD, which further compromises their academic success and social functioning. Executive-function (EF) deficits are a core feature of ADHD and are known to affect reading in RD, yet their specific impact on Chinese reading remains under-explored. Objective This study investigated how EF deficits influence Chinese reading in children with ADHD, with the goal of informing diagnosis and intervention for ADHD-RD comorbidity. Methods This study recruited 160 Chinese-speaking children who met DSM-5 criteria for ADHD and allocated them to two groups—ADHD-only (n = 80) and ADHD + RD (n = 80). ADHD symptoms were rated with the Swanson, Nolan and Pelham Teacher and Parent Rating Scale (SNAP-IV), whereas Chinese reading was evaluated with the Dyslexia Checklist for Chinese Children (DCCC). Executive functions were measured with tasks tapping visuospatial working memory, verbal working memory, and response inhibition (Go/No-Go). Results Both groups showed no significant differences in ADHD symptom scores. Compared with the ADHD-only group, the ADHD + RD group obtained higher total and subscale DCCC scores and lower accuracies on EF tasks. Total DCCC scores correlated negatively with EF performance, especially on visuospatial working-memory and response-inhibition tasks. Conclusion This study suggests that individuals with ADHD comorbid with Chinese reading disabilities (RD) exhibit more pronounced deficits in executive function, particularly in verbal and visual-spatial working memory, and response inhibition tasks, compared to individuals with ADHD alone. These cognitive deficits are significantly negatively correlated with Chinese reading abilities, emphasizing the importance of not only focusing on traditional ADHD symptoms but also prioritizing training to enhance executive functions, especially visual-spatial working memory and response inhibition, when diagnosing and treating patients with ADHD comorbid with RD, in order to improve their reading abilities.